The Use of Canon Law in Ecclesiastical Administration, 1000-1234
1 online resource.
Keywords: The Use of Canon Law in Ecclesiastical Administration, 1000-1234 explores the integration of canon law within administration and society in the central Middle Ages. Grounded in the careers of ecclesiastical administrators, each essay serves as a case study that couples law with social, political or intellectual developments. Together, the essays seek to integrate the textual analysis necessary to understand the evolution and transmission of the legal tradition into the broader study of twelfth century ecclesiastical government and practice. The essays therefore both place law into the wider developments of the long twelfth century but also highlight points of continuity throughout the period. Contributors are Greta Austin, Bruce C. Brasington, Kathleen G. Cushing, Stephan Dusil, Louis I. Hamilton, Mia Münster-Swendsen, William L. North, John S. Ott, and Jason Taliadoros.